Application of Diffusion Tensor Imaging (DTI) in the Diagnosis of HIV-Associated Neurocognitive Disorder (HAND): A Meta-Analysis and a System Review - Ma, Juming; Yang, Xue; Xu, Fan; Li, Hongjun (Frontiers in Neurology, 2022)
ABSTRACT Background: The patients with HIV-associated neurocognitive disorder(HAND) are often accompanied by white matter structure damage. Diffusion tensor imaging (DTI) is an important tool to detect white matter structural damage. However, the changes in DTI values reported in many studies are diverse in different white matter fiber tracts and brain regions. Purpose: Our research is dedicated to evaluating the consistency and difference of the correlation between HAND and DTI measures in different studies. And the value of DTI in HAND evaluation, so as to obtain consensus and independent conclusions between studies. Method: We searched PubMed and Web of Science to collect relevant studies using DTI for the diagnosis of HAND. After screening and evaluating the search results, meta-analysis is used for quantitative research on data. Articles that cannot collect data but meet the research relevance will be subjected to a system review. Results: The meta-analysis shows that the HAND group has lower fractional anisotropy (standardized mean difference=-0.57 p＜0.0001)and higher mean diffusivity(standardized mean difference=0.04 p＜0.0001) than the healthy control group in corpus callosum. In other white matter fibers, we found similar changes in fractional anisotropy (standardized mean difference=-1.18 p＜0.0001) and mean diffusivity(standardized mean difference=0.69 p＜0.0001). However, the heterogeneity (represented by I2) between the studies is high(in corpus callosum 94%, 88%, in other matter fibers 95%, 81%). After subgroup analysis, the heterogeneity is obtained as 19.5%, 40.7%(FA, MD in corpus callosum) and 0%, 0% (FA, MD among other white matter fibers). Conclusion:The changes in white matter fibers in patients with HAND are statistically significant at the observation level of DTI compared with healthy people. The differences between the studies are mainly derived from demographics, start and maintenance time of antiretroviral therapy, differences in nadir CD4+T cells and the use of different neurocognitive function scales. As an effective method to detect the changes of white matter fibers, DTI is of great significance for the diagnosis of HAND, but there are still some shortcomings. In the absence of neurocognitive function scales, independent diagnosis remains difficult. Keywords: Meta-analysis, HIV-associated neurocognitive disorder(HAND), Diffusion Tensor Imaging(DTI), Fractional Anisotropy (FA), Mean Diffusivity (MD)